2019
DOI: 10.4330/wjc.v11.i12.316
|View full text |Cite
|
Sign up to set email alerts
|

Left recurrent laryngeal nerve palsy following aortic arch stenting: A case report

Abstract: BACKGROUNDAortic arch stenting is continuously emerging as a safe and effective option to alleviate aortic arch stenosis and arterial hypertension.CASE SUMMARYWe present a 15-year-old girl with aortic arch hypoplasia who had undergone implantation of an uncovered 22 mm Cheatham-Platinum stent due to severe (native) aortic arch stenosis. On follow-up seven months later, she presented a significant re-stenosis of the aortic arch. A second stent (LD Max 26 mm) was implanted and both stents were dilated up to 16 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The obtained results on the topographic anatomical interrelations of the left recurrent laryngeal nerve and the aortic arch correspond with the data of individual authors [13][14][15][16] .…”
supporting
confidence: 86%
“…The obtained results on the topographic anatomical interrelations of the left recurrent laryngeal nerve and the aortic arch correspond with the data of individual authors [13][14][15][16] .…”
supporting
confidence: 86%
“…12 Literature review demonstrated only 1 case report of a patient who developed vocal cord paralysis secondary to recurrent laryngeal nerve injury after re-stenting of coarctation of the aorta and the patient recovered with no intervention within 6 months. 13 While the statistical significance of this finding was not calculated, it raises the possibility that recurrent laryngeal nerve injury secondary to interventional congenital catheterisation procedures is of lower risk than cardiothoracic surgery. Interventional procedures may cause a stretch or compression phenomenon of the left recurrent laryngeal nerve versus true injury during surgical procedures.…”
Section: Discussionmentioning
confidence: 95%
“…The RLN passes directly underneath the aortic arch. Subsequent nerve stretching caused left RLN palsy, which was recovered in advance [ 17 ]. Also, the other endovascular surgery with aortic stent-graft placement can entail left VCP.…”
Section: Discussionmentioning
confidence: 99%